“JUST” - a reading module: an innovation report - Lim, Geoffrey F. C.; Hussain, Mohamad Noh Mustafah; Abdul Jalil, Norshamshizar; Mohamad, Maslawati (Universiti Teknologi MARA, 2024)
Reading, especially in English as Second Language (ESL), is always one of the most important language skills emphasised by educators globally. Reading and vocabulary are interrelated in a reading class. However, a reading module that compiles reading aloud, reading comprehension and vocabulary is still not being widely used among learners and teachers in Malaysia. Reading comprehension was one of the main problems faced by the learners in secondary school. Thus, this study aimed to design, develop and evaluate a reading module for the pupils in lower secondary school. The module was developed by applying the five stages of the ADDIE (analysis, design, development, implementation, evaluation) model. The design and development of this reading module were underpinned by whole-language theory. The evaluation of this reading module was conducted using pre and post-test amongst 23 pupils in a school in Kuala Lumpur. The results were analysed descriptively by comparing the score of pre and post-test. The main findings showed pupils’ reading ability significantly improved after using this reading module. Therefore, this reading module is pedagogically feasible for lower secondary school pupils. The favourable outcomes also demonstrate how using a reading module in an ESL classroom helps pupils strengthen their reading ability.